Plasma level of soluble urokinase‐type plasminogen activator receptor as a predictor of disease severity and case fatality in patients with bacteraemia: a prospective cohort study - Huttunen, R.; Syrjänen, J.; Vuento, R.; Hurme, M.; Huhtala, H.; Laine, J.; Pessi, T.; Aittoniemi, J. (Journal of internal medicine, 2011)
Huttunen R, Syrjänen J, Vuento R, Hurme M, Huhtala H, Laine J, Pessi T, Aittoniemi J (Tampere University Hospital; University of Tampere Medical School, University of Tampere; Centre for Laboratory Medicine, Pirkanmaa Hospital District; University of Tampere Medical School; School of Health Sciences, University of Tampere; and Medical School, University of Tampere; Tampere, Finland) Plasma level of soluble urokinase‐type plasminogen activator receptor as a predictor of disease severity and case fatality in patients with bacteraemia: a prospective cohort study. J Intern Med 2011; 270: 32–40. .  Objectives.  Urokinase‐type plasminogen activator receptor (uPAR) is expressed on a variety of different immune cells and vascular endothelial cells during inflammation. Previous studies indicate that a high plasma concentration of the soluble form of the receptor (suPAR) predicts poor outcome in infectious diseases. Design.  A prospective cohort study. Subjects and methods.  Plasma suPAR levels were measured in 132 patients with bacteraemia caused by Staphylococcus aureus, Streptococcus pneumoniae, ß‐haemolytic streptococcae or Escherichia coli using a commercial enzyme‐linked immunosorbent assay (ELISA). Values were measured on days 1–4 after a positive blood culture, on days 13–18 and on recovery. Results.  The maximum suPAR values on days 1–4 were markedly higher in nonsurvivors compared to survivors (15.8 vs. 7.3 ng mL−1, P < 0.001) and the area under the receiver operating characteristic curve (AUCROC) in the prediction of case fatality was 0.84 (95% confidence interval (CI) 0.76–0.93, P < 0.001). At a cut‐off level of 11.0 ng mL−1, the sensitivity and specificity of suPAR for fatal disease was 83% and 76%, respectively. A high level of suPAR (≥11 ng mL−1) was associated with hypotension (mean arterial pressure <70 mmHg) (odds ratio (OR) 6.5; 95% CI 2.9–14.6) and high sequential organ failure assessment score (≥4) (OR 9.3; 95% CI 4.0–21.9). A high suPAR level remained an independent risk factor for case fatality in a logistic regression model adjusted for potential confounders. Conclusion.  Plasma suPAR level is a sensitive and specific independent prognostic biomarker in patients with bacteraemia.